Representation of Sovereign Power and Its Resistance in Wonka (2023): Barthes' Semiotics Analysis - Fitra Hanif; Fikri Arya Nurrachman; Muhammad Faisal Rahmadin (Publikasi Inspirasi Indonesia, 2025)
This study explores the representation of power relations, particularly sovereign power and resistance, in the film